2016
DOI: 10.1136/bjophthalmol-2015-307868
|View full text |Cite
|
Sign up to set email alerts
|

Boston keratoprosthesis type I in the elderly

Abstract: Boston type I keratoprosthesis is an effective modality in corneal blindness in elderly patients. Failure to restore or maintain ambulatory vision was typically due to non-corneal comorbidities, often unrelated to the keratoprosthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…20,23,44 Among patients who received a KPro, 1 patient (25%) developed a retrolenticular membrane, which is lower compared with previously reported rates of 33% to 45.5%. 19,25 In our study, an individual who underwent PKP developed a non-expulsive suprachoroidal hemorrhage. While this complication is rare, it has been previously described after corneal transplant with an estimated occurrence of 0.73%.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…20,23,44 Among patients who received a KPro, 1 patient (25%) developed a retrolenticular membrane, which is lower compared with previously reported rates of 33% to 45.5%. 19,25 In our study, an individual who underwent PKP developed a non-expulsive suprachoroidal hemorrhage. While this complication is rare, it has been previously described after corneal transplant with an estimated occurrence of 0.73%.…”
Section: Discussionmentioning
confidence: 85%
“…20,23,44 Among patients who received a KPro, 1 patient (25%) developed a retrolenticular membrane, which is lower compared with previously reported rates of 33% to 45.5%. 19,25…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with short-term studies, better retention rates were observed in non-cicatrizing conditions, ranging from 77% to 97.3%. 19,28,35,38,40,44,50 In contrast, in autoimmuneassociated cicatrizing conditions such as SJS or MMP, retention rates were significantly lower (range 37.5-55%). 42,43 Alexander and colleagues reported that most retention failures in SJS were due to sterile corneal necrosis (78%; 14/18 eyes).…”
Section: Anatomical Retentionmentioning
confidence: 96%
“…Adicionalmente, os pacientes com aniridia eram mais jovens do que os do grupo comparativo. A prevalência de glaucoma aumenta com a idade 80 , embora o efeito da idade no glaucoma relacionado ao B-KPro tipo 1 não tenha sido totalmente investigado 81 .…”
Section: Outras Complicações Após a Cirurgia De B-kpro Tipounclassified